PERAN STRES KERJA, MOTIVASI, DAN WORK-LIFE BALANCE TERHADAP KEPUASAN KERJA SERTA DAMPAKNYA TERHADAP KINERJA KARYAWAN - Subagyo, Luthfina Tsabitah; Meria, Lista (JURNAL LENTERA BISNIS, 2025)
Employee performance is a crucial factor in determining organizational productivity, particularly for production operators, who play a strategic role in supporting the smooth running of the manufacturing process. This study aims to analyze the influence of work stress, motivation, work-life balance, and job satisfaction on the performance of production operator employees. This study used a quantitative approach, involving 130 respondents selected through purposive sampling. Data collection used a questionnaire, and analysis was conducted using the Structural Equation Modeling – Partial Least Squares (SEM-PLS) method. The results show that work-life balance, motivation, and job satisfaction have a positive effect on employee performance, while work stress has a negative effect on employee performance. Furthermore, work stress has also been shown to decrease work-life balance, job satisfaction, and performance. These findings provide practical contributions for companies in developing performance improvement policies based on employee welfare.